Management of pediatric blunt abdominal trauma - Shater, Wassem Ameer; Nasser, Mohammad Ali; Alloush, Ali Mohammad (Journal of medical and pharmaceutical sciences, 2021)
Aim of study: Evaluating a non- operative treatment of pediatric blunt abdominal trauma and avoiding unnecessary surgical intervention in Tishreen University Hospital.Methods: During years (2016- 2020) a retroprospective study was conducted on 62 children who had isolated blunt abdominal trauma or associated with other injuries, most of them were managed by non- operative treatment but some required surgical management.Results: Non- operative management of pediatric blunt abdominal injuries was applied for 59 patients, three patients required a surgical procedure, the spleen was the most organ exposed to injury (40) child, followed by liver (26) child, kidney (4) and (1) pancreatic injury. Non- operative management was successful in most solid organs injuries with grades 1, 2 and 3, but it failed in 5 grade splenic injury. one out of two hollow viscus injuries required surgical intervention. There were no statistical differences between the study groups in age, gender and injury mechanism. Hospital length of stay was significantly longer in patients who underwent a laparotomy (6) days compared to other non- operative patients (3) days, one complication occurred during non- operative management as pseudocyst after pancreatic injury, (4) patient died in the non- operative group due to hemodynamic instability and associated severe cerebral injuries.Conclusion: It is safe to treat most children with blunt abdominal injuries non- operatively if monitoring is adequate with hemodynamic stability.
Keywords: Blunt abdominal injuries; Pediatric trauma; Surgical management